2021
DOI: 10.1557/s43578-021-00214-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of indentation size and spacing on statistical phase analysis via high-speed nanoindentation mapping of metal alloys

Abstract: The development of high-speed nanoindentation has enabled the acquisition of mechanical property maps over square millimeters of area with micron-scale resolution in reasonable amounts of time. This provides rich datasets which contain morphological and statistical data on the variation of mechanical properties in a microstructure. However, the influences of the indentation size and the deconvolution method employed on the extracted phase properties remain unclear. In this work, a range of depth/spacing increm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Material phase properties generally vary depending on composition, heat treatment and texture, particularly when dealing at nano-scale. [7][8][9][10] The weld deposit containing the hard carbide phases were found to be sensitive to cooling procedures. The microstructural modification, morphology variation (refer Figure 1 and 4) and changes in local elemental composition due to heat treatments were evident.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Material phase properties generally vary depending on composition, heat treatment and texture, particularly when dealing at nano-scale. [7][8][9][10] The weld deposit containing the hard carbide phases were found to be sensitive to cooling procedures. The microstructural modification, morphology variation (refer Figure 1 and 4) and changes in local elemental composition due to heat treatments were evident.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that some of the studies have endeavoured to measure directly the strength of matrix phase with or without the influence of grain boundaries through nano-scale tests. 9,12,[22][23][24][25] For example, the hardness of martensite matrix phase alone was measured by Ohmura et al 24 and ferrite matrix alone in micro-alloyed steels by Lee et al 25 Rodriguez et al 12 analysed the influence of indentation size on the mean hardness and elastic modulus of martensite, pearlite and ferrite phases of steels and the results were reported as a function of nanoindentation depth. Besharatloo et al 9 reported that the 'α' ferrite phase showed higher elastic modulus compared to the 'γ' austenite phase in duplex stainless steel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant trend pervading this focus issue is the strongly increasing use of nanoindentation as a high-throughput method for producing large amounts of data [26][27][28][29][30][31], which are then analyzed with emerging data science algorithms. The former is made possible through recent technical developments by hardware manufacturers which aim at performing a single indentation within no more than 1 s (KLA: Express Test and NanoBlitz, Bruker: XPM, Alemnis: UHSR, and others).…”
Section: Big Datamentioning
confidence: 99%
“…This allows for the measurement of large mappings of up to 100,000 indents within 1-2 days. Such large datasets are then statistically analyzed, e.g., by machine learning algorithms [26]. The aim of such studies Introduction ADVANCED NANOMECHANICAL TESTING Introduction is generally to access the intrinsic mechanical properties of the different components of modern alloys and composite materials.…”
Section: Big Datamentioning
confidence: 99%